Improving Program Quality and Competitiveness through House of Quality Driven Service in Wellness Startup - Syifa, Naufal Dhamiri; Basri, Mursyid Hasan (Universitas Muhammadiyah Surakarta, 2023)
Wellness is a fundamental aspect that every human must achieve to become substantially human. The wellness industry itself, predicted to grow significantly for the next few years. Sadly, many people, particularly millennial workers, are unaware of wellness, including their own. Many millennial workers suffer from stress, sadness and anxiety. This is made even more worse by post-COVID-19 conditions that force workers to work from home, making it increasingly difficult for them to be able to separate their professional and personal lives. To solve the problem, Mealth is present by bringing programs and activities that aim to spread awareness about wellness itself and also implementing wellness into their lives. However, wellness itself has eight dimensions and Mealth has only adapted a few programs related to one of those dimensions. The aim of this study is to establish a new program so that Mealth can develop its program into other wellness dimensions according to customer preferences using the House of Quality framework. This study will use a qualitative approach, by selecting the informant sampling from Mealth customers and wellness enthusiasts through a semi-structured interview method. The result of the interview will be analyzed using the House of Quality framework as a tool to develop new Mealth services. This research finds that the new program that Mealth want to develop is related into three aspects, which is sport community partnership, environmental workshop & education, and creativity & new skill workshop.